PENGARUH PENGGUNAAN MEDIA PUZZLE TERHADAP KEMAMPUAN BERHITUNG PENJUMLAHAN PESERTA DIDIK KELAS II SDN BULUREJO 1 JOMBANG - Istiani, Yayuk; Susilo, Claudya Zahrani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low ability to calculate the addition of grade II elementary school students due to mathematics learning that is still abstract and lacks the use of concrete media. This study aims to determine the ability to calculate the addition of students before and after the implementation of the use of puzzle media and to determine the effect of the use of puzzle media on the ability to calculate the addition of grade II students of SDN Bulurejo 1 Jombang. The research method used is quantitative research with a pre-experimental method using a one group pretest-posttest design. The research subjects were 29 grade II students. The data collection technique used a test of the ability to calculate the addition, while data analysis was carried out through the Shapiro-Wilk normality test and hypothesis testing using the Paired Sample t-test. The results showed an average pretest score of 68.27 with a percentage of completion of 41.37%, while the average posttest score increased to 89.65 with a percentage of completion of 100%. The results of the Paired Sample t-test showed a significance value of 0.000 (sig. < 0.05). Based on these results, it can be concluded that the use of puzzle media has a significant effect on the addition calculation abilities of second-grade students at SDN Bulurejo 1 Jombang.